2016
DOI: 10.18632/oncotarget.11089
|View full text |Cite
|
Sign up to set email alerts
|

G-protein-coupled receptors mediate ω-3 PUFAs-inhibited colorectal cancer by activating the Hippo pathway

Abstract: Colorectal cancer (CRC) is one of the most common cancers leading to high mortality. However, long-term administration of anti-tumor therapy for CRC is not feasible due to the side effects. Omega-3 polyunsaturated fatty acids (ω-3 PUFAs), particularly DHA and EPA, exert protection against CRC, but the mechanisms are unclear. Here, we show that ω-3 PUFAs inhibit proliferation and induce apoptosis of CRC cells in vitro and alleviate AOM/DSS-induced mice colorectal cancer in vivo. Moreover, ω-3 PUFAs promote phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 48 publications
0
42
1
Order By: Relevance
“…Our previous studies show that linoleic acid (an n-6 LCFA) and EA (a trans fatty acid), enhance colon carcinogenesis or metastability of CRC ( 5 , 6 , 9 , 10 ), whereas docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) (n-3 LCFAs) suppress colon carcinogenesis and enhance efficacy of chemotherapy regimens ( 27 ). The n-3 LCFAs also activate the hippo system via GPR40 and GPR120 to inhibit proliferation of CRC ( 28 ). Although blood TG level is widely utilized as a predictive clinical parameter, the identity of the fatty acids that constitute the TGs might be an important factor that determines the relationship between TGs and cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies show that linoleic acid (an n-6 LCFA) and EA (a trans fatty acid), enhance colon carcinogenesis or metastability of CRC ( 5 , 6 , 9 , 10 ), whereas docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) (n-3 LCFAs) suppress colon carcinogenesis and enhance efficacy of chemotherapy regimens ( 27 ). The n-3 LCFAs also activate the hippo system via GPR40 and GPR120 to inhibit proliferation of CRC ( 28 ). Although blood TG level is widely utilized as a predictive clinical parameter, the identity of the fatty acids that constitute the TGs might be an important factor that determines the relationship between TGs and cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…O3FAs can exert anti-CRC activity following their interaction with surface free fatty acid (FFA) G protein-coupled receptors (GPCRs), thereby activating pro-apoptotic signalling [ 17 ]. These GPCRs have been shown to be expressed on non-epithelial cells such as adipocytes [ 38 , 39 ] and macrophages [ 40 ], on which activation can alter macrophage polarisation and reduce inflammation that is potentially important for anti-cancer activity of O3FAs.…”
Section: Preclinical Data Supporting the Anti-crc Activity Of O3fasmentioning
confidence: 99%
“…In terms of COX-independent activity, both DHA and EPA have been shown to act as ligands for and inhibit cell proliferation via GPCRs such as GPR120 [ 44 ]. More recently, it has been reported that this interaction leads to the activation of the Hippo signalling pathway in LoVo and HT29 cells in vitro [ 17 ]. In vivo , GPCR activation resulted in a reduction in tumour burden in the azoxymethane (AOM)/dextran-sulphate model in Balb / c mice fed a 10% fish oil diet [ 17 ].…”
Section: Preclinical Data Supporting the Anti-crc Activity Of O3fasmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that the Hippo/YAP pathway can crosstalk with other signalling pathways to regulate a series of biological functions in cancer, which is greatly depends on the important role of YAP that is not only mediated by the upstream signal molecule, but can also regulate a series of targets via interacting with transcription factors. By analysing studies published in recent years, we can summarize a complex regulatory network in which YAP is involved in a series of signalling pathways (Figure 1 ), such as those involving TGF-β/SMAD [ 67 , 68 ], Wnt/β-catenin [ 69 , 70 ], epidermal growth factor receptor (EGFR) [ 39 , 71 ], PI3K-AKT [ 72 , 73 ], NF-κB [ 69 , 74 ], Sonic Hedgehog (Shh) [ 75 , 76 ], mTOR [ 77 , 78 ], IL6 receptor (IL-6R) [ 79 , 80 ], GPCR [ 81 , 82 ], and Notch [ 83 , 84 ].…”
Section: Introductionmentioning
confidence: 99%